Community Empowerment Strategy Based on Social Entrepreneurship Values Through Village-Owned Enterprise in Indonesia: The Contribution for Social Studies Education - Widiastuti, Anik; Mulyani, Endang; Riani, Lilia Pasca; Saputri, Agatha; Samsudin, Norsamsinar (Universitas Negeri Yogyakarta, 2024)
BUMDes or Village-Owned Enterprise (VOE) as the spearhead of the Indonesian Government's extension in solving poverty problems in rural areas is still not performing optimally because it has faced many problems for which solutions have not yet been found. A holistic strategy is needed to cover various aspects and involve various parties to achieve VOE goals. This research examines various community empowerment strategies based on social entrepreneurship values through VOE. This is qualitative descriptive research. The data used is primary data from the in-depth interviews with informants by determining informants using the snowball sampling method, observation, and documentation. Secondary data was obtained from research results published in journals indexed by Dimension, Sinta, and Google Scholar as well as news from the official websites of credible institutions. The unit of analysis for this research is 6 VOE in the Special Region Provinces of Yogyakarta and Central Java, Indonesia. The research results show that there are 5 strategies for community empowerment based on social entrepreneurial values through VOE, namely 1) economic-based empowerment; 2) environment-based empowerment; 3) arts-culture and local wisdom-based empowerment; 4) community-based empowerment; and 5) village asset management-based empowerment. The research results can be adapted and adopted by other VOE as an effort to empower the community by choosing one of the strategies that is most relevant to the problems that occur, available resources, and the characteristics of the local community.